2015
DOI: 10.1002/2014wr016155
|View full text |Cite
|
Sign up to set email alerts
|

Lowland fluvial phosphorus altered by dams

Abstract: Dams affect ecosystems, but their physical link to the variations in fluvial fluxes and downstream ecological consequences are inadequately understood. After estimating the current effects of the Three Gorges project and other reservoirs upstream on the Yangtze River on the fluvial phosphorus (P) in the middle and lower Yangtze River, we further investigated the long-term effects of dams on the fluvial regimes of P and P-enriched sediment (PES). Simultaneously measured P distributions with sediment size (PDSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…A one-dimensional, nonuniform sediment model was applied to model the transport and deposition of different-sized sediments in the TGR. Modeling work was described in detail by Zhou and Lin (1998) and Zhou et al (2015). The entire TGR was defined with 432 cross sections as computational nodes from ZT to the dam site, including 756 km in the mainstem and 65 and 67 km in the tributary backwater areas of the Jialing and Wu Rivers, respectively.…”
Section: Sediment Modeling and Predictionmentioning
confidence: 99%
“…A one-dimensional, nonuniform sediment model was applied to model the transport and deposition of different-sized sediments in the TGR. Modeling work was described in detail by Zhou and Lin (1998) and Zhou et al (2015). The entire TGR was defined with 432 cross sections as computational nodes from ZT to the dam site, including 756 km in the mainstem and 65 and 67 km in the tributary backwater areas of the Jialing and Wu Rivers, respectively.…”
Section: Sediment Modeling and Predictionmentioning
confidence: 99%
“…In another work on lateral flow, Zhou et al . [] investigated the long‐term effects of dams on fluvial regimes of P and P‐enriched sediment using simultaneously measured P distributions and sediment size. Their computations revealed that a reservoir would significantly lower the downstream availability of P in the dry season and promote high pulses of P in summer when the reservoir is flushed as sedimentation accumulates.…”
Section: Summary Of Papersmentioning
confidence: 99%
“…On the other hand, because of the high affinity of many contaminants to fine mineral particles, e.g., phosphorus and nickel, the dynamic circulation, temporal-spatial distribution and final destination of such contaminants are closely related to the fine sediment movement. Especially, the previous wash-load is now becoming the major part of deposition and one of the main medium of contaminants for the relative quiescent water bodies like artificial reservoirs and lakes, as recent human interposition on rivers has changed the paths of sediment significantly [7][8][9]. Therefore, laboratory experiments on such contaminant with fine sediment in fluvial environment and other aquatic ecosystem attracts more and more attentions [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Flume experiments as a tool of study have been widely used observing the mechanism of sediment transport in fluvial environment [3,14,15]. As some important particle affinity contaminants are overwhelmingly adsorbed on and regulated by sediment [7,8,11,12,16], thus flumes should also be used as an effective tool in simulating the mobility and dynamic behaviors of such an eco-matter and contaminant in rivers, along with the transport, deposition and re-suspension of sediment [11,13,17]. However, fine suspended sediment experiments in laboratory flumes is usually inaccurate and hardly repeatable because of the difficulties in accurate loading both in rate and composition and the unavoidable recirculation of the sediment from the outlet to inlet of a flume, which can modify the input conditions significantly in particular for the eco-related fine sediment due to its lightness and long distance adjustment in relative short flumes.…”
Section: Introductionmentioning
confidence: 99%